Chronic type 2 reaction possibly triggered by an asymptomatic Bartonella henselae infection in a leprosy patient - Luciene Silva dos Santos; Marina Rovani Drummond; Andrea Fernandes Eloy da Costa França; Maria Helena Postal Pavan; Rafael Fantelli Stelini; Maria Letícia Cintra; Elemir Macedo de Souza; Paulo Eduardo Neves Ferreira Velho (Revista do Instituto de Medicina Tropical de São Paulo, 2022)
ABSTRACT As leprosy and leprosy reactions are the most prevalent infectious cause of physical disability, it is important to commit efforts to better understand these chronic reactions. Infections, even when asymptomatic, can trigger leprosy reactions and Bartonella spp. in turn, can cause chronic infections. We presented a case of a 51-year-old man who was admitted presenting with chronic type 2 leprosy reactions. He had a lepromatous form of leprosy that was histologically diagnosed six months after the onset of signs and symptoms compatible with a chronic type 2 reaction. He reported a history of a previous hepatitis B diagnosis. During a 24-month multidrug therapy (MDT), chronic reactions were partially controlled with prednisone and thalidomide. Thirty-three months following the leprosy treatment, he still experienced chronic reactions, and whole bacilli as well as globi were found on a new skin biopsy. Since coinfections can trigger type 2 reactions and the patient had close contact with animals and ticks, we investigated the presence of a Bartonella sp. infection. Bartonella henselae DNA was detected in a skin fragment obtained before the beginning of the leprosy retreatment. However, even after six months of a second leprosy MDT, he continued to experience type 2 chronic reactions. He was admitted to the hospital to undergo an intravenous antibiotic therapy for 14 days and then complete the treatment per os for ten more weeks. Leprosy reactions improved following the treatment for B. henselae. After completing the MDT treatment, he has been accompanied for sixty months with no signs of leprosy or leprosy reactions. The asymptomatic infection by B. henselaein this patient was considered the putative trigger of chronic leprosy reactions and leprosy relapse.